De la mano de Dios. El nacionalismo católico chileno y la Guerra del Pacífico, 1879-1881 - McEvoy, Carmen (2004)
This article analyzes the role played by the Catholic Church’s intellectual elite in the construction of a nationalistic discourse during the War of the Pacific, 1879-1884. This nationalistic rhetoric, which served the interests of the Chilean state, purified the conflict of its political and economic connotations, and conferred upon it a sacred and eternal justification. Cultural agents, through the carefully calculated use of the means of communication, converted the idea that Divine Providence supported the Chilean cause into a driving force. By means of its participation in this ideological debate and by mobilizing civil society, the Chilean church probably aimed to defend its preeminent role as the main cultural frame of reference in the face of the threat posed by other social actors which disputed its hegemony during that period.